Collaborating to develop agricultural skills: Capacity-building agencies in the United States of America - Peterson, Donna J.; Downey, Laura H.; Farrell, Bryan C. (Food and Agricultural Organization of the United Nations, 2021)
Investing in farmers – or agriculture human capital – is crucial to addressing challenges in our agri-food systems. A global study carried out by the FAO Investment Centre and the International Food Research Institute, with support from the CGIAR Research Programme on Policies, Institutions and Markets and the FAO Research and Extension Unit, looks at agriculture human capital investments, from trends to promising initiatives. One of the nine featured case studies comes from the State of Mississippi in the United States of America. Agencies from i) formal education systems; (ii) nonformal education systems; (iii) state governmental agencies; and (iv) advocacy and commodity groups collaborated to develop agriculture human capital among youth and adults. Agency documents, representatives and clients described technical skills and functional skills developed, resulting in benefits like increased agricultural productivity, reduced expenses, higher individual or farm income, networks linking farmers and other producers, a better prepared workforce and a strong agriculture industry with good economic returns. This publication is part of the Country Investment Highlights series under the FAO Investment Centre's Knowledge for Investment (K4I) programme.